The effect of intra-articular ozone injection on pain and physical function in knee osteoarthritis: A prospective study - Gülçin Gazioğlu Türkyılmaz; Mesut Bakır; Şebnem Rumeli Atıcı (National Scientific Medical Center, 2020)
Introduction: This study aims to evaluate the effect of intra-articular ozone treatment on pain and physical functionality by measuring Numerical Pain Rating Scale (NRS), WOMAC Osteoarthritis Index (WOMAC-OI), and Active Joint Range of Motion (AROM) in patients diagnosed with osteoarthritis. Material and methods: A total of 30 patients diagnosed with stage 2-3 osteoarthritis according to the Kellgren-Lawrence Classification System (K-L) were included in the study. Ozone gas was administered (10 ml of 10 mcg/ml per session) twice weekly for a total of four sessions. AROM examination was performed at pre-treatment baseline (BL), post-treatment (PT), and two weeks after treatment (PT2). During these periods, NRS was assessed and WOMAC-OI questionnaire was administered. Results: Significant improvement in NRS and WOMAC-OI total index scores were observed at PT and PT2 periods compared to BL (6.9±1.2; 2.1±1.3; 3.3±1.1; WOMAC-OI total index: 48.1±10.1; 25.5±10.4; 29.1±11.1 respectively; p˂0.001 for all). However, in both of these evaluation methods, the recovery at PT2 had decreased compared to the PT period (NRS p˂0.001; WOMAC-OI p˂0.05). Significant improvement was observed in the AROM values measured during the PT and PT2 periods, compared to baseline (105.6 ± 10.4°; 118.8 ± 8.1°; 117.5 ± 9.2°, respectively) (p˂0.001). There was no difference between the PT and PT2 periods in terms of AROM measurements (p˃0.05). Conclusion: Our study demonstrates that intra-articular ozone injection treatment provides improvement in pain and physical functionality in osteoarthritis patients. In our two-month follow-up assessment, although evaluation methods indicated that there was regression in recovery, AROM measurements showed that there was no regression in function. Therefore, we believe that future studies may include AROM as an objective measurement among evaluation methods.